Patient Satisfaction in Negative Pressure Rooms, Dental Teaching Hospital, Universitas Trisakti - Rizka Nur Meilizza; Tri Erri Astoeti; Tiarma Talenta Theresia (Faculty of Dentistry, Universitas Trisakti, 2025)
Background: Negative pressure rooms in dental hospitals are built to mitigate the risks of COVID-19, viruses, and other infectious diseases, ensuring the safety of patients, dentists, nurses, and the overall hospital environment. Patient satisfaction is a priority, measured through the Service Quality (Servqual) framework, which evaluates five dimensions: Tangibles, Responsiveness, Reliability, Assurance, and Empathy. Additionally, the Importance-Performance Analysis (IPA) method can identify key questions and dimensions prioritized in quadrant I. Objective: To assess patient satisfaction in the negative pressure room at the RSGM-P FKG USAKTI academic clinic. Methods: A descriptive observational study was conducted using a cross-sectional research design involving 109 participants. Data collection utilized a questionnaire that included 30 questions focused on importance and 30 questions focused on performance. Results: Patients expressed satisfaction with the services provided in the negative pressure room at KIH RSGM-P Trisakti University, achieving an average performance score of 3.61 and an importance score of 3.7. Conclusion: Patients are satisfied overall, but two dimensions that require improvement are responsiveness and assurance. Key areas for enhancement include the speed of response to patient complaints, operators' knowledge, communication skills, and nursing services.